(untitled) (Bioagro, 2025)
Lettuce is the most consumed leafy crop worldwide and the high levels of nitrates in its leaves can be carcinogenic. The objective of this study was to evaluate the effect of different nitrate/ammonium ratios in the nutrient solution and two light intensities (200 and 400 μmol·m⁻²·s⁻¹) on the growth and nutrient concentration of lettuce plants under hydroponic conditions. Controlled environment chambers (light and temperature) and a floating root system were used with the application of Steiner’s nutrient solution modified for each of the treatments. Treatments consisted of combinations of three nitrate/ammonium ratios (100/0, 75/25, and 50/50) and two LED light intensities. The variables evaluated were root volume, fresh and dry weight of the leaves, dry weight of the root, total dry weight and the mineral composition of the leaves. The experimental design was completely randomized with a 3 × 2 factorial arrangement with six repetitions. For the statistical analysis of the data, an analysis of variance and a comparison of means test were performed (Tukey, p≤0.05). The results showed that increasing the proportion of ammonium reduced the volume and dry weight of the root without affecting the fresh weight of the leaf. Increasing the light intensity increased the root volume and the fresh and dry weight of the leaves, while ammonium reduced the levels of potassium, calcium and nitrates in the leaves, especially when an intensity of 400 μmol·m⁻²·s⁻¹ was applied. These results suggest that optimizing nitrate/ammonium ratios and light conditions improves biomass production and nutritional quality of hydroponic lettuce.